ANALISIS KONSEP PEMBELAJARAN GEOMETRI MELALUI ARSITEKTUR MASJID AGUNG SYAHRUN NUR SIPIROK KABUPATEN TAPANULI SELATAN - Siregar, Yulia Pratiwi; Siregar, Enni Sari (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to determine the extent of understanding of the material of plane and spatial shapes through the architecture of the Grand Mosque of Syahrun Nur Sipirok. The research method used in this study is descriptive qualitative. This research data was obtained by using observation and structured interviews. The data analysis technique used is triangulation using four steps, namely 1) Description, 2) Reduction/Focus, 3) Selection, 4) Conclusion. The study began with the identification of the problems found and then determined the focus of the problem, namely finding the concept of learning geometry through an in-depth study of the architecture of the Grand Mosque of Syahrun Nur. Data were obtained from 11 respondents who were visitors to the Mosque who were still high school students, based on the results of interviews conducted with respondents, it can be concluded that learning carried out by the method of direct introduction to learning objects is more effective in increasing students' understanding of the material of plane and spatial shapes than conventional learning which only focuses on theories and examples that are abstract and difficult to interpret. Analysis carried out on tourist objects around us can make learning more enjoyable so that the set learning objectives are achieved optimally.